America's war on terror - Lansford, Tom.; Covarrubias, Jack.; Covarrubias, Jack.; Lansford, Tom.; Watson, Robert P.; Watson, Robert P. ([S.l.] : Ashgate, 2009)
Developing ideas established in the successful first edition, this new version of "America's War on Terror" updates and expands the original collection of essays, allowing the reader to fully understand how the causes of the war on terror, both the domestic and foreign policy implications, and the future challenges faced by the United States have moved on since 2003. The features include: four specifically designed sections which examine the topic from different perspectives and orientations to provide a balanced and nuanced understanding of the issues; new material takes into account events through the election of Barack Obama and potential changes in the US-led war on terror; four additional core chapters look at Homeland Security, Afghanistan, Pakistan and Central Asia, Iraq and the Persian Gulf and Globalization, all with a focus on the War on Terror; a robust introduction builds on the previous preface, while the editors have also developed a concluding section that brings together the major themes of the work and provides an overview of future policy challenges and options; the book's existing tables and appendices are also completely updated; and, essays written from a variety of perspectives provide instructors with a useful tool to supplement course materials. The book also offers the student an analytical means with which to understand the factors behind the attacks, the nation's response to them, and the continuing evolving impact of terrorism on domestic and international politics. "America's War on Terror, Second Edition" will be of interest and utility to academics, the general public and most significantly to students as a reader for such courses as US foreign policy, international security, terrorism, Islamic studies, and, American politics and international relations.
Keywords: Bush, George W. (George Walker), 1946-; Diplomatic relations; Obama, Barack; United States; War on Terrorism (2001-2009)